A preliminary conservation genetic study of Pittosporum obcordatum (Pittosporaceae), an endemic New Zealand species with a disjunct distribution. Issue 4 (2nd October 2017) - Wright, Sarah A.; Hutchison, Melissa; Hale, Marie L.; Gemmill, Chrissen E. C.; de Lange, Peter J.; Pelser, Pieter B.
ABSTRACT: Pittosporum obcordatum (Pittosporaceae; heart-leaved kōhūhū) is an endemic New Zealand plant species that is classified as Threatened–Nationally Vulnerable. It has a disjunct distribution and is only known from relatively few and small populations. Using 10 Inter-Simple Sequence Repeat markers (ISSRs), we studied patterns of genetic diversity and genetic differentiation among eight out of the c. 14 populations of this species to inform its conservation management. Pittosporum obcordatum has low genetic diversity at the population level (uHe = 0.169) compared to other long-lived and outcrossing species, but genetic diversity is relatively high in comparison with several other threatened species. Spearman's Rank Correlation Coefficients suggest significant positive correlations between population size and genetic diversity as measured by the percentage of polymorphic loci and uHe . Pittosporum obcordatum also shows relatively high levels of genetic differentiation among populations (AMOVA-derived, P < 0.001; all pairwise Φst values P < 0.05), indicating low genetic connectivity. Populations with relatively few plants are therefore prone to further reductions in genetic diversity through inbreeding and genetic drift. Of these, especially the Kaitaia, Owen Valley and Paengaroa populations are of conservation concern, because they contain private alleles, and therefore notably contribute to the genetic diversity of P. obcordatum .